Usability of technological tools to overcome language barriers in healthcare– a scoping review - Annika Kreienbrinck; Saskia Hanft-Robert; Alina Ioana Forray; Asithandile Nozewu; Mike Mösko (Archives of Public Health)
Abstract Introduction In many healthcare contexts globally, where the languages of care providers and service users do not match, miscommunication can lead to inaccurate diagnoses and subpar treatment outcomes. The development and use of technological tools to overcome language barriers are increasing, but usability and evaluation of these tools vary widely. Objectives This scoping review’s objectives are (i) to identify and describe the technological tools used in direct service user–provider communication to overcome language barriers in a healthcare setting, (ii) to identify how the usability of these tools was evaluated, and (iii) to identify the challenges and benefits of using such technological tools. Methods and analysis The scoping review followed the JBI methodology. Studies published between January 2019 and July 2024 were identified using a search strategy with variations of the keywords “technological tools,” “language barrier,” and “health care” in the following six databases and research platforms: PubMed, PsycArticle, Scopus, EBSCOhost, ProQuest, and Web of Science. All literature on individuals using a technological tool to overcome language barriers in a healthcare context was included and exported into the screening assistant software Rayyan. The search was limited to articles written in German or English. The literature was screened twice by three independent reviewers in a blinded fashion, and all relevant data were presented in a descriptive summary. Results Based on 16 publications, this scoping review identified 16 technological tools, categorized as fixed-phrase or machine translation apps, to overcome language barriers in a healthcare setting. Usability was assessed in 13 publications applying diverse methods, i.e., surveys, observations, and application data analysis. Technological tools hold potential as a means to address language barriers in healthcare by facilitating communication and supporting diagnostic processes. However, their usability is often constrained by challenges related to translation accuracy, accessibility, and learnability. Conclusion Future research and policy efforts should focus on standardizing evaluation methods and diversifying development regionally, linguistically, and interdisciplinary. Rather than broadly promoting these tools, emphasis should be placed on ensuring they are reliable and efficient for their intended use to maximize their effectiveness and relevance in specific healthcare contexts.